ChemInform Abstract: Sulfonamide and Tertiary Amine as Nucleophiles in Pd(II)‐Catalyzed Diamination of Alkynes: Synthesis of Tetracyclic Indolobenzothiazine S,S‐Dioxides - Ha, Tu M.; Yao, Bo; Wang, Qian; Zhu, Jieping (ChemInform, 2016)
A high‐yielding three‐step preparation of the title products is described consisting of a Sonogashira‐coupling of 2‐iodobenzenesulfonamides with N‐2‐(methoxycarbonyl)ethyl protected 2‐alkynylaniline, Pd‐catalyzed intramolecular diamination, and removal of the N‐protecting group.